Remembering Dr Li-Ching Lee, a pioneer of global autism research. (February 2022) - Rubenstein, Eric; Rice, Catherine; Hollingue, Calliope; Tsai, Peng-Chou; Stewart, Lydia; Daniele Fallin, M
The field of global autism research lost a pioneer, champion, and innovator with the passing of Dr Li-Ching Lee in May 2021. Dr Lee served as the editor for a special issue in Autism on global autism research (2017, Volume 21, Issue 5) and her substantial impact on autism research and autistic individuals and their families in low- and middle-income countries warrants a place in this special issue. While a giant in the professional arena, her large impact on science is minor compared to the compassion, kindness, and love she brought to her family, friends, and her professional communities at Johns Hopkins, across institutions, her native Taiwan, and the areas in which she conducted her research. Dr Lee was immensely humble and intensely focused on harnessing epidemiology to positively impact the lives of people with autism and developmental disabilities. Her humility and professional dedication was coupled with a desire to keep her own challenges and triumphs private including her courageous efforts to stave off cancer while accomplishing so much in support of others.